Electrical parameters and ion species for active transport in human esophageal stratified squamous epithelium and Barrett's specialized columnar epithelium - Tobey, N. A.; Argote, C. M.; Vanegas, X. C.; Barlow, W.; Orlando, R. C. (American journal of physiology: Gastrointestinal and liver physiology, 2007)
The human esophagus is lined by stratified squamous epithelium (ESSE), and in some subjects with reflux disease the distal esophagus becomes lined by Barrett's specialized columnar epithelium (BSCE). ESSE and BSCE differ both histologically and functionally, the latter evident by differences in their in vivo transmural electrical potential difference (PD), ESSE averaging −15 mV and BSCE being greater than −25 mV. In this report we examine the basis for this difference in PD. This is done by mounting endoscopic biopsies of ESSE from 25 subjects without esophageal disease and BSCE from 19 with Barrett's esophagus in mini-Ussing chambers for electrical recordings basally and after bathing solution ion replacement. The results show that the PD of human ESSE reflects a low level of active ion transport (5.1 ± 0.8 μA/cm 2 ) combined with a high level of tissue (electrical) resistance (344 ± 34 Ω·cm 2 ) and that of BSCE reflects a high level of active transport (43.6 ± 11.6 μA/cm 2 ) combined with a low level of resistance (69 ± 8 Ω·cm 2 ). Furthermore, active transport in ESSE was principally due to sodium absorption whereas in BSCE it was equally divided between sodium absorption and anion (chloride/bicarbonate) secretion, the latter through an apical membrane, 4-acetamido4′-isothiocyano-2,2′-stilbenedisulfonic acid-sensitive anion channel. As an anion-secreting tissue with bicarbonate secretory capacity more than fivefold greater than ESSE, BSCE is better suited than ESSE for defense of the esophagus against reflux disease.